Psychological features of feelings of guilt in Uzbek women - Dilfuza Farhodovna, Djurakulova (International Journal of Psychosocial Rehabilitation, 2020)
This article gives an overview of the feelings of guilt, the causes, psychological features, and mechanisms of Uzbek women involved in various labor activities. The marital status and occupation of women are analyzed, and the degree of guilt of unmarried young girls and married women engaged in various types of work is examined using various methods. They find that the level of altruism and egotism is higher in women who have a higher level of altruism and are more likely to feel guilt and vice versa. The article deals with the peculiarities of the working mentality of women and the problems they face, and the topic is explored experimentally. The article also explores the relationship between age characteristics and gender differences in feelings of guilt and theoretically and practically analyzes age and gender differences. The article deals with the psychological characteristics of feelings of guilt in Uzbek women and their peculiarities in human activities.